Medical students’ perception of international health electives in the undergraduate medical curriculum at the College of Medicine, King Saud University - Fouda Neel A; AlAhmari LS; Alanazi RA; Sattar K; Ahmad T; Feeley E; Khalil MS; Soliman M (Advances in Medical Education and Practice, 2018)
Abdullah Fouda Neel,1 Leena Saad AlAhmari,2 Reema Ayed Alanazi,3 Kamran Sattar,4 Tauseef Ahmad,4 Elizabeth Feeley,4 Mahmoud Salah Khalil,4 Mona Soliman4 1College of Medicine, Alfaisal University, Riyadh, Saudi Arabia; 2Department of Family Medicine and Polyclinics, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 3College of Medicine, King Saud University, Riyadh, Saudi Arabia; 4Department of Medical Education, College of Medicine, King Saud University, Riyadh, Saudi Arabia Background: International health electives prepare medical students during their student years of medical education in choosing, matching, and succeeding in the residency of their choice. They serve as a unique educational experience prior to residency training.Objective: This study was conducted to explore 4th- and 5th-year medical students’ perspective about international health electives and to evaluate their educational effects.Methods: An anonymous online survey with 22 items concerning perceptions about the electives with a 5-point Likert scale was administered to medical students at the College of Medicine, King Saud University.Results: For the majority of the students (81.6%) the elective course was arranged by the university and only 18.4% of students individually arranged their own. Most of the students (65.7%) agreed that the objective of the elective course was clear to them in advance. A total of 71.1% of students agreed that the program (elective) was responsive to their needs (both academically and socially).Conclusion: This is the first study looking at international electives in the context of the undergraduate medical curriculum in Saudi Arabia. The study showed that the international electives are a useful and unique experience for medical students (both academically and socially). Keywords: medical students, perception, international electives, experience, Saudi Arabia